2023
DOI: 10.3389/fsoc.2023.982946
|View full text |Cite
|
Sign up to set email alerts
|

Undertaking rapid evaluations during the COVID-19 pandemic: Lessons from evaluating COVID-19 remote home monitoring services in England

Abstract: IntroductionRapid evaluations can offer evidence on innovations in health and social care that can be used to inform fast-moving policy and practise, and support their scale-up according to previous research. However, there are few comprehensive accounts of how to plan and conduct large-scale rapid evaluations, ensure scientific rigour, and achieve stakeholder engagement within compressed timeframes.MethodsUsing a case study of a national mixed-methods rapid evaluation of COVID-19 remote home monitoring servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…A review of rapid ethnographies in healthcare found only a few peer-reviewed articles addressed dissemination efforts and recommended that future researchers who do so design dissemination strategies that do not reduce the richness of the data (Vindrola-Padros and Vindrola-Padros, 2018). Within healthcare we found non-ethnographic examples of dissemination of actionable protocols and briefs that were informed by the findings (Higham et al, 2022;Walton et al, 2023). The rapid conversion of findings to action through the dissemination of protocols underscores the institutional endorsement of the research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of rapid ethnographies in healthcare found only a few peer-reviewed articles addressed dissemination efforts and recommended that future researchers who do so design dissemination strategies that do not reduce the richness of the data (Vindrola-Padros and Vindrola-Padros, 2018). Within healthcare we found non-ethnographic examples of dissemination of actionable protocols and briefs that were informed by the findings (Higham et al, 2022;Walton et al, 2023). The rapid conversion of findings to action through the dissemination of protocols underscores the institutional endorsement of the research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some ways of quickly building rapport and trust include: sharing and discussing early thoughts on the proposed design of the study; demonstrating commitment by showing up consistently to meetings to indicate a shared priority; listening to stakeholders' priorities and concerns and indicating that these have been heard; being flexible; delivering as promised; and promptly sharing study findings. 107…”
Section: Delivering Difficult or Uncertain Findingsmentioning
confidence: 99%